Experiences of a Fine Dining Event Held Inside a Working Prison - McIntosh, Alison; Harkison, Tracy (Routledge, 2024)
Fine dining experiences offered inside working prisons are one type of hospitality initiative attempting to support prisoner rehabilitation and offer a memorable dining experience for the paying public. Previous hospitality research has not explored how fine dining delivered in a working prison, offered through this type of social initiative, is experienced by those involved: the inmates volunteering in the event, the celebrity chefs who mentor them, paying diners and other event stakeholders. This case study research examined the “Gate to Plate” fine dining event held inside Rimutaka men’s prison in New Zealand. We analysed publicly available material online about this hospitality initiative to discern the key experiences of those involved. Thematic analysis of the data revealed four main themes relating to the experiences of those involved in the fine dining event: a quality food and meal experience; pride and passion arising from being involved; skills for change; and shifted perceptions. While the case study research revealed positive experiences of the prison’s fine dining event and suggested it was a potentially transformative experience for all those involved in it, we critically discuss wider implications of the event, and the positive portrayals by all those involved, for hospitality initiatives in working prisons.
Keywords: 35 Commerce, Management, Tourism and Services; 3504 Commercial Services; 3506 Marketing; 44 Human Society; 3508 Tourism; 4402 Criminology